Policy issues and options in aquatic food systems: Review of frameworks, tools, and studies - Ragasa, Catherine; Loison, Sarah Alobo (International Food Policy Research Institute, 2022)
Although policies can be critical constraining or enabling factors for aquatic food systems (AqFS) development, scarce evaluation of the impacts of existing policies means that decision-makers have limited understanding of how to improve the design and implementation of effective policies. This paper reviews key policy issues in AqFS and how they have been analyzed and assessed to provide context-tailored policy options and guidance. Our review shows that countries face many policy issues but have little analysis on them. Despite the availability of a wide variety of frameworks, concepts, tools, methods, and approaches, their application in empirical analysis to solve policy issues in AqFS has been limited. More research is available on local- and community-level governance of fisheries, but less on national or subnational policies and regulations in AqFS. The few available policy studies focus on developed countries, with fewer applications in developing countries where growth of the aquaculture and fisheries sectors is much stronger. The studies provide useful policy options and guidance, and this review highlights the need for more such studies to address policy-related issues in the sector.